In vitro analysis of high resistance and low expansion dental plasters available in Peru - Cruzado-Oliva, Fredy Hugo (2023)
Objective. To compare the hardness, dimensional stability, and compressive strength of high-strength, low-expansion dental plasters available in Peru, according to ADA criteria. Methods. A descriptive, observational and cross-sectional study was developed. A selection of 8 cylindrical-shaped samples and 8 rectangular- shaped ones, from seven high-resistance, low-expansion dental plasters were fabricated. The hardness was evaluated using the Identec Universal Durometer. Dimensional stability was evaluated with a digital caliper and compressive strength was evaluated with the Instron Universal Testing Machine. To determine if there is a difference in each of these properties, the analysis of variance, F test, and the Duncan’s test were used. In addition, to assess whether these values differ from those of the ADA, the mean comparison test, student’s t table, were used. Results. The hardness, dimensional stability and average compressive strength of the high-strength, low-expansion dental plasters showed that there are significant differences (p<0.05) between each of the dental plasters and with the standard averages established by the American Dental Association. (ADA). Conclusions. 100% of the high-strength, low-expansion dental casts meet the parameters established by the ADA in terms of their compressive strength, only 28.6% of these comply with the ADA in terms of dimensional stability and that 100% of these do not meet the average hardness standards established by the ADA.